Isolation of Thermophilic Bacteria from Bora Hot Springs in Central Sulawesi - Slamet Ifandi; Muh Alwi (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Thermophilic bacteria can survive at high temperature, in which hot spring is one of its habitats. Indonesia has many hot springs with potential as a habitat for thermophilic bacteria. The purpose of this study was to obtain isolates thermophilic bacteria from Bora hotspring located in Central Sulawesi. This study applied a descriptive-observational study design, characteristics of bacterial properties identified using conventional methods according to the Bergey’s Manual of Determinative Bacteriology. The study was conducted in 3 stages. The first stage was bacteria cultivation on the appropriate media, followed by stage of isolated and the last stage by identified characteristics of thermophilic bacteria which included microscopic and macroscopic morphology, Physiological and biochemistry test. The results of the isolates indicted 4 representative isolated of thermophilic bacteria from Bora Hot Spring namely TM022, TM023, TM024, TM026. The bacteria isolates obtained were bacillus, coccus and Gram negative and positive, while the physiological test of all isolates were able to grow and showed changes in the medium. This study is useful in providing characteristic of indigenous thermophilic bacteria isolates that produces thermostable enzymes.